Activity Centred Signature Pedagogies for the Creation of Digital Educational Publications - Bülow, Morten Winther; Nørgård, Rikke Toft; Goodyear, Peter (Proceedings of the International Conference on Networked Learning, 2024)
In this paper, we draw together three sets of ideas to create a framework for understanding and improving the networked creation of digital educational artefacts. We combine ideas on learning networks and networked learning, activity-centred analysis and design (ACAD) and signature pedagogies. Focusing on establishing a framework for understanding the network practices, the participation of people from different professions and the nature of learning in doing, the paper explores the possibility of constructing a framework that can be customised to the needs of specific professions or of industry-specific multi-professional networks. The case on which we focus, and which we use to inform, illustrate and sharpen some of the argument, is that of digital educational publishing – specifically, the activity of the educational publishing company Systime. However, we see the framework as applicable to a much more extensive range of situations. Consequently, the paper contributes to wider theoretical and practical work on the creation of digital educational artefacts. It also contributes to thinking more deeply about assumptions and practices involved in professional knowledge-building networks: especially where participants develop what we describe as a ‘reflexive designerly disposition’, capable of improving what a network achieves and how it functions.